An Efficient Battery Charger Control Scheme for Electric Vehicles - Shyla Shree M; Mahendra MB (Journal of Power Electronics and Devices, 2022)
This work suggests a practical control scheme for a battery charger for an electric car that employs a cascade of buck converters and symmetrical bridge-less power factor-corrected converters. Both converters are increasingly common in the industrial sector thanks to their high efficiency, low price, and small size. The entire battery charging mechanism is made substantially more efficient by integrating the two converters. Furthermore, at any input voltage, this charger’s design can deliver the correct battery current and voltage without ripple. In order to achieve a unity input power factor and zero input current harmonic distortion, the proposed control approach employs duty ratio feed-forward control technique in both the current and voltage control loops. In addition, a phase-locked loop (PLL) block establishes the current loop’s reference, producing a pure sinusoidal input current despite the input voltage waveform’s distortion. The viability and utility of the suggested approach are demonstrated using simulation and experimental data with an 110V/60Hz ac line input and a 1.5kW-72V dc output of the battery charging system.